Measurement of liquid refractive index by quantitative phase reconstruction of single frame dual-wavelength digital hologram. (January 2023) - Huang, Meng; Sun, Chan; Qin, Hongpeng; Jiang, Zhuqing
Highlights: Liquid refractive index measurement by using single frame dual-wavelength hologram. No requirement of another hologram of refractive-index-known liquid as a reference. Measuring the refractive indices of salt and sucrose solutions at five concentrations. Application in the measurements of physical parameters of liquid via refractive index. Abstract: A measurement method of liquid's refractive index by means of single-shot dual-wavelength off-axis digital holographic microscopy system and a microfluidic chip is presented. The refractive index of liquid filled in the microchannel of a microfluidic chip can be calculated directly with the unwrapped phase map obtained at the synthetized wavelength, without requirement of knowing another liquid's refractive index as a measurement reference. Moreover, it also avoids the influence of the accuracy of the known refractive index on the refractive index to be measured. The refractive indices of salt solutions and sucrose solutions in the several concentrations are achieved in the experiments, which verifies that the measurement of liquid's refractive index is accurate and reliable. With the merit of accurate measurement of liquid's refractive index based on the one-frame dual-wavelength hologram, it is expected that this approach will be employed to detect in real-time the fluid's parameters related to its refractive index.